2018
DOI: 10.1155/2018/9276260
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Phytochemistry and Pharmacological Activities of Clinacanthus nutans (Burm.f.) Lindau

Abstract: Clinacanthus nutans (Burm.f.) Lindau (Acanthaceae), commonly known as Sabah snake grass, is a vegetable and a well-known herb that is considered an alternative medicine for insect bites, skin rashes, herpes infection, inflammation, and cancer and for health benefits. Current review aims to provide a well-tabulated repository of the phytochemical screening, identification and quantification, and the pharmacological information of C. nutans according to the experimental design and the plant preparation methods w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 64 publications
0
56
0
Order By: Relevance
“…The results of the LC/MS/MS analyses of the C. nutans ethanolic leaf extract in this study demonstrated the presence of myricetin, orientin, iso-orientin, vitexin, iso-vitexin, isookanin, apigenin and ferulic acid as some of the important bioactive compounds of the plant. However, three of these compounds-myricetin, isookanin and ferulic acid-were additional compounds identified in the C. nutans ethanolic leaf extract cultivated in Pahang-Malaysia, which were not among the compounds identified earlier by Huang et al [17] and Chelyn et al [18], as well as other recent literatures as reported by Khoo et al [31].…”
Section: Discussionmentioning
confidence: 56%
“…The results of the LC/MS/MS analyses of the C. nutans ethanolic leaf extract in this study demonstrated the presence of myricetin, orientin, iso-orientin, vitexin, iso-vitexin, isookanin, apigenin and ferulic acid as some of the important bioactive compounds of the plant. However, three of these compounds-myricetin, isookanin and ferulic acid-were additional compounds identified in the C. nutans ethanolic leaf extract cultivated in Pahang-Malaysia, which were not among the compounds identified earlier by Huang et al [17] and Chelyn et al [18], as well as other recent literatures as reported by Khoo et al [31].…”
Section: Discussionmentioning
confidence: 56%
“…C. nutans has been used as a traditional medicine in Southeast Asia, including Thailand, Malaysia, and Indonesia, for treating skin rashes, snake and insect bite, dysuria, gout, and diabetes [ 17 , 18 , 19 , 20 ]. In Thailand, this plant is in the national list of essential medicines for treatment of herpes simplex and varicella-zoster virus (VZV) infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, various phytochemicals presented in C. nutans extract have been reviewed and a range of phytochemical compounds including flavonoids, triterpenoids, steroids, phytosterols, and glycosides have been demonstrated [ 19 , 20 ]. Only a few studies have reported the biological activities of the compounds identified as potential bioactive compounds in this study, and most of them were related to anti-inflammatory and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…There were extensive phytochemistry studies, isolating many compounds from C. nutans, trying to investigate the anti-cancer effects of these isolated compounds. These flavonoids and terpenoids were also commonly isolated from various other plants [41,42].…”
Section: Discussionmentioning
confidence: 94%
“…Previous study [42] published extensive metabolite profiling of C. nutans extracts. The research team identified betulin, lupeol and beta-sitosterol (Sigma Aldrich, USA) in stem extracts, which were not identified from other C.nutans extracts.…”
Section: Discussionmentioning
confidence: 99%